Why Are More Women Working in Britain? - Joshi, Heather E.; Layard, Richard; Owen, Susan J. (Journal of Labor Economics, 1985)
In Britain, female labor force participation rose steadily from the Second World War to 1977. To explain this, we estimate a pooled time-series, cross-section supply function for single-year age groups of women. The life-cycle pattern is explained quite well by the presence of children. At a second stage we try to explain the rising level of the cohort intercepts estimated at the first stage. Real wage growth may be an explanatory factor, as cross-section evidence suggests it should be. Finally, we point to the 15% rise in the relative pay of women in the mid-1970s caused by the Equal Pay Act. This did not cause the expected decline in the relative demand for female employees.